Online learning models for junior high school students in the era of the COVID-19 pandemic - Fatchur Rohman; M. Lutfi Hidayatullah; Riska Roisatul Ajizah; Endah Junita Sari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
In this era of the COVID-19 pandemic, many students experience obstacles in their learning process, especially in implementing online learning models. The purpose of the community service program is to apply online learning models and media that can be used in learning in the era of the COVID-19 pandemic. This program is intended for teachers and students at MTs SA PP Roudlotut Tholibin in Bandungharjo Village, Donorojo District, Jepara Regency. The implementation stages of the program include the development of learning tools and media, the application and process of making learning media, the use of website-based learning applications, and mentoring and application of web-based learning applications. The results of the community service program are guidelines for using web-based learning applications and innovative learning media. The results of the program show that the application of online learning models with innovative media can improve teacher performance and student understanding. Teachers can use creative media properly. Students' understanding has increased in learning during the COVID-19 pandemic.